Evaluation of malnutrition status and clinical indications in children with celiac disease: a cross-sectional study - Zahra Setavand; Maryam Ekramzadeh; Naser Honar (BMC, 2021)
Abstract Background Celiac Disease (CD) is an autoimmune systemic disorder triggered by gluten in genetically susceptible individuals, which can lead to chronic malabsorption. Considering the changes in the manifestations of CD, this study aimed to determine anthropometric indices and clinical indications in children with CD. Methods This cross-sectional study aimed to evaluate the children with CD who had referred to Imam Reza Celiac Clinic between 2016 and 2019. Totally, 361 children were eligible and their anti-tissue transglutaminase (TGA-IgA) level, weight, height, and Body Mass Index (BMI) were extracted from their records. The anthropometric indices were presented based on the criteria of the Center for Disease Control and Prevention (CDC) and World Health Organization (WHO). The prevalent symptoms were assessed, as well. Results Based on the CDC's criteria, 18.3, 28.8, and 25.8% of the children had short stature, low body weight, and low BMI, respectively. These measures were obtained as 10, 22.4, and 13.9% according to the WHO's categorization respectively. Furthermore, the most common symptoms among the children were abdominal pain (56.5%), skeletal pain (28%), constipation (27.4%), and anemia (23.8%). Conclusion To sum up, the results clearly indicated that growth failure and low height, weight, and BMI were prevalent among the children with CD. Moreover, in addition to gastrointestinal symptoms, a considerable number of patients had skeletal pain and anemia.